Prediction on Ground Settlement Deformation and Influence of Urban Buildings in the Construction Process of Existing Tunnel Reconstruction. (16th March 2022) - Liu, Minghui; Yin, Aiguo; Wan, Cong
Abstract : Surface deformation is one of the key issues in urban tunnel construction control, regardless of the construction method. The study on ground settlement deformation and urban buildings in the construction process of existing tunnel reconstruction is not many at present; moreover, rebuilding projects for older tunnels have more complicated planting conditions and limited construction methods. In this study, the construction method and process characteristics of an existing structure are analyzed. In addition, the ground settlement deformations and building displacements during construction are monitored. The results reveal that the method of the Peck formula for predicting the ground settlement deformation and urban buildings of existing tunnel reconstruction is feasible and effective based on fitting curve by monitoring data. A finite element model is established. The results show that the simulation values of the ground deformation are consistent with the measured values. The differences between the simulated and measured values of the maximum ground surface sedimentation are 4.9% and 0.72% for single-sided excavation and bilateral excavation, respectively. The maximum building settlement is -9.6 mm in the single-sided excavation, the deformation rates remain within 0.1 mm/d, and the maximum width change of the building crack occurs during the demolition of the existing tunnel concrete in the single-sided excavation (with a value of 0.45 mm); subsequently, the building crack exhibits a decreasing trend, indicating that the crack is stable. The results can provide a reference for construction control for existing tunnels.